Three new monoterpene glycosides from Sibiraea laevigata (L.) Maxim. (March 2017) - Zhao, Jian-Qiang; Wang, Yan-Ming; Wang, Qi-Lan; Shao, Yun; Shi, Yan-Ping; Mei, Li-Juan; Tao, Yan-Duo
Graphical abstract: Highlights: Three new monoterpene glycosides (1 –3 ) were isolated from Sibiraea laevigata (L.) Maxim. Fourteen known compounds (4 –17 ) were also obtained from the title plant. All of the isolated compounds were evaluated for their anti-oxidant and α-glucosidase inhibitory activities. Compounds7 and17 exhibited α-glucosidase inhibitory effect with IC50 values of 220.0 and 113.0 μM, respectively. Abstract: Three new compounds, 3, 7-dimethy-7-methoxy-3-octene-5-one-1- O - β -d -glucopyranoside (1), 3, 7-dimethy-7-methoxy-3( Z )-octene-5-one-1- O - β -d -glucopyranoside (2) and 3, 7-dimethy-3-hydroxy-6-octene-5-one-1- O - β -d -glucopyranoside (3), together with fourteen known compounds (4–17) were isolated from the leaves and shoots of S. laevigata . The structures of the new compounds were elucidated on the basis of extensive spectroscopic analysis, including one- and two-dimensional NMR, as well as mass spectral data. All isolates were evaluated for their α-glucosidase inhibitory and antioxidant activities. The results demonstrated that 3, 7-dimethyl-3(Z), 6-ocatdien-5-one-1- O - β -d -glucoside (7) and sitosteryl β -d -glucoside (17) exhibited α-glucosidase inhibitory effects with IC50 values of 220.0 and 113.0 μM, respectively.